MANGROVE FOR FUTURE: GERAKAN PENANAMAN MANGROVE SEBAGAI SOLUSI PELESTARIAN PESISIR DI PULAU HARAPAN - Supriatiningsih, Supriatiningsih; Febrianti, Wenty; Rizaldy, M. Asmi; Ibrahim, Luckman; Kaunang, Sandra DE; Ruseno, Ndaru; Abdulah, Budiman; Suryaningsih, Maria; Ramdany, Ramdany; Ghofir, Ade; Maftuchah, Viniyati; Darwis, Hidayat; Rizal, Moch; Santoso, Imam; Suhana, Suhana; Susilawati, Susi; Mulyanti, Rita Yuni; Mahroji, Dwi (EDELWEISS: Jurnal Pengabdian Masyarakat, 2026)
Coastal areas face various environmental pressures, such as abrasion, ecosystem degradation, and reduced mangrove vegetation cover due to human activities and environmental change. Harapan Island, in the Seribu Islands, is one of the coastal areas with a vital mangrove ecosystem, both as a natural coastal barrier and as a habitat for marine life. However, the condition of the mangroves in this area still requires strengthening through conservation and rehabilitation activities involving the community. The "Mangrove for Future" program was designed as a community service activity based on mangrove planting on Harapan Island, with the aim of increasing community ecological awareness, strengthening coastal conservation efforts, and encouraging community participation in environmental rehabilitation. The implementation method included preparation, outreach and education, mangrove planting, and monitoring and evaluation. The implementation results showed that the mangrove planting program was able to increase community understanding of the ecological function of mangroves, encourage community and youth involvement in conservation activities, and has the potential to strengthen coastal protection from abrasion in the long term. This program also demonstrated that mangrove conservation not only has ecological impacts but also contributes to social strengthening of coastal communities through the growth of collective concern for the environment. Thus, the mangrove planting movement on Harapan Island can be a real solution for sustainable coastal conservation